An experimental study of solids deposited on the base of a heated vessel at low pressure. (25th May 2017) - Elsaye, E.A.; McNeil, D.A.; Salem, S.M.; Rylatt, D.; Baker, S.
Abstract: The life expectance of some industrial evaporators is constrained by the rate of corrosion of the heated surfaces, with larger temperatures producing larger corrosion rates. Some process fluids contain dissolved materials that produce solid particles when the fluid is evaporated. These solids can form beds of particles on the heated base of the evaporator vessel or be suspended in the fluid. The presence of these particles may have an effect on the temperature of the heated surfaces and hence their corrosion rate. The effect on temperature of two very different particles are investigated, glass and Caesium Phosphomolybdate particles (Cs3 (MoO3 )12 PO4 ·14H2 O). The later is referred to as CPM. The glass particles had diameters of 500–600 μm, a specific gravity of 2.2 and a bed depth variation of 0–32 mm. The CPM particles had diameters of the order of 10 μm, a specific gravity of 4.0 and a bed depth variation of 0–50 mm. The effect of the glass particles was investigated while heating water at a pressure of 50 mbar absolute. The CPM particles were investigated while heating a water solution at a pressure of 65 mbar absolute. The evaporator used was a model industrial boiler slice. The boiler test section was 1 m high, 0.75 m wide and 98 mm long. The evaporator contained 36 electrically heated tubes to simulate the presence of heated coils. The design of the boiler ensured that the tubes, which were 28.5 mm in diameter, were always submerged in a liquid pool. The tube heat flux was maintained at 65 kW/m 2 and the base heat flux varied within the range 0–45 kW/m 2 . When a base heat flux was applied the glass particles remained within a bed formed on the base of the evaporator, whereas the CPM particles became suspended in the fluid. In both cases, the temperature in the liquid pool is shown to be reasonably constant and close to the free surface saturation value. The bed of glass particles induced boiling on the surface below it at most conditions, increasing the local base temperature and therefore the local corrosion rate. The base remained in free convection outside of the bed, producing lower base temperatures and therefore a lower corrosion rate. The CPM particles did not form a bed on the base of the evaporator and the temperature of the base remained in free convection at temperatures below, or close to, the local saturation value. However, some base heating was evident near the base centre. The presence of CPM type particles is unlikely to affect the corrosion rate.